THE USE OF FOLKLORISMS IN A. ABDIEV'S NOVEL-DIALOGUE "ANCIENT KARAKALPAKS" - Allamuratova, Zukhra Makhsetbaevna; Kaipbergenova, Azada Muratbayevna (SCIENCE and SOCIETY, 2026)
The article analyzes the use of folklorisms in writer Allanazar Abdiyev's novel-dialogue "Ayyemgi qaraqalpaqlar" Through the folklorisms used in this work, the connections between folklore and literature are revealed.
Keywords: folklore; mythology; legend; tale; novel; tradition; typology; image